STRATEGI HUMAS KOTA BANDUNG DALAM MENYUSUN CONTENT PILLAR MEDIA SOSIAL - Fadilla, Rashina Zahra; Ghozali Moenawar, Mohamad; Suparman; Muhammad, Badar; Firdaus, Diky; Manisya, Nabhila; Putri Awalina, Salwa (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2024)
This study discusses the success of Bandung City Public Relations in managing social media as a means of disseminating public information. The use of social media proves that Bandung City Public Relations can adapt to the digital era. The use of appropriate social media strategies and content pillars makes Bandung City Public Relations an exemplary example for other government agencies. Bandung City Public Relations can prove that implementing appropriate content pillars in managing social media, can break the perception that information provided by the government to the public is always rigid. This study uses a descriptive qualitative approach with thematic and content analysis methods. Data collection was carried out through interviews, observations, and literature studies. This study resulted in a discussion of the strategy for compiling Bandung City Public Relations' social media content pillars, the compilation of which was carried out simultaneously with the preparation of content planning. Bandung City Public Relations uses an agenda-setting strategy in implementing social media content planning. Bandung City Public Relations carries out three stages of the agenda-setting process which include the stages of determining the public agenda, defining the media agenda, and determining the policy agenda. Bandung City Public Relations' social media has three main content pillars, namely eduvative content, functional content, and entertaining content. The three pillars are applied to every social media account of Bandung City Public Relations, the packaging of which is adjusted to the characteristics of each social media. Bandung City Public Relations strives for content packaging that is not rigid to increase the level of interaction with the public.